Investigation on SCR-based ESD protection device for biomedical integrated circuits in a 0.18-μm CMOS process. Issue 11 (November 2015) - Lin, Chun-Yu; Chiu, Yan-Lian
Abstract: In these decades, integrated circuits for biomedical electronics applications have been designed and implemented in CMOS technologies. In order to be safely used by human, all microelectronic products must meet the reliability specifications. Therefore, electrostatic discharge (ESD) must be taken into consideration. To protect the biomedical integrated circuits in CMOS technologies from ESD damage, a dual-directional silicon-controlled rectifier (DDSCR) device was presented in this work. Experimental results show that the DDSCR has the advantages of high ESD robustness, low leakage, large swing tolerance, and good latchup immunity. The DDSCR was suitable for ESD protection in biomedical integrated circuits.